Integrated Multianalyte Second-Tier Testing for Newborn Screening for MSUD, IVA, and GAMT Deficiencies - Graham B. Sinclair PhD, FCCMG; Manuel Ester; Gabriella Horvath MD, PhD, FRCPC, FCCMG; Clara D. van Karnebeek MD, PhD, FRCPC, FCCMG; Sylvia Stockler-Ipsirogu MD, FRCPC; Hilary Vallance MD, FCCMG (Journal of Inborn Errors of Metabolism and Screening, 2016)
Advances in mass spectrometry have allowed for expansion of newborn screening test panels over the last decade but with increased numbers of disorders have come increased concerns with false-positive rates. The introduction of second-tier testing has improved the specificity of screening for a number of disorders without any corresponding sacrifice in sensitivity. Such testing does, however, put pressure on scarce laboratory resources including instrument and personnel time and even the bloodspot sample itself. The British Columbia Newborn Screening Program has developed an integrated second-tier screening approach to improve test performance without the requirement to resample and reprocess the original bloodspot specimen. By utilizing the residual extract from the first-tier assay and introducing a chromatography step as the second tier, we have been able to reduce false-positive rates due to interfering isobaric compounds for 3 different disorders (maple syrup urine disease, isovaleric aciduria, and guanidinoacetate methyltransferase) in a single multianalyte assay.